2020
DOI: 10.26460/md.v4i2.8577
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Loyalitas Pegawai Terhadap Promosi Jabatan Pada Dinas Perumahan Dan Kawasan Permukiman Kabupaten Bima

Abstract: This study aims to determine and analyze the effect of significant employee loyalty to the promotion of positions at the Bima Regency Housing and Settlement Office. The type of research used is associative, with a sample of 68 respondents. The sampling technique used was purposive sampling. Data collection using a questionnaire with a Likert measurement scale. Data analysis methods used are validity test, reliability test, simple linear regression, simple correlation, determination test and t test (two parties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
2
1
1
Order By: Relevance
“…Previous research conducted by [6] and [7] found a positive and significant impact of employee loyalty on job promotions, contrary to the research by [8], which found that loyalty had no influence on job promotions.…”
Section: Introductioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Previous research conducted by [6] and [7] found a positive and significant impact of employee loyalty on job promotions, contrary to the research by [8], which found that loyalty had no influence on job promotions.…”
Section: Introductioncontrasting
confidence: 66%
“…Job promotion plays a significant role for every employee. According to Bambang Wahyudi in [7], indicators of job promotion consist of: 1) Honesty, 2) Loyalty, 3) Level of Education, 4) Work Experience, and 5) Initiative.…”
Section: Job Promotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loyalitas kerja merupakan salah satu faktor yang mempengaruhi promosi jabatan, karena karyawan yang memiliki loyalitas kerja tinggi dianggap mampu memberikan hasil yang maksimal dalam pencapaian tujuan perusahaan [16]. Penelitian lain mendapatkan hasil bahwa motivasi yang diberikan pimpinan akan berpengaruh terhadap loyalitas karyawan, dimana tingkat loyalitas karyawan yang tinggi akan berpengaruh terhadap promosi jabatan [17]. Penelitian yang berbeda mendapatkan hasil bahwa loyalitas karyawan berpengaruh positif terhadap promosi jabatan, dimana loyalitas kerja merupakan salah satu faktor timbulnya promosi jabatan [18].…”
Section: Paroliunclassified